Validation of the Spanish version of the Oral Health Impact Profile (OHIP-14Sp) in elderly Chileans - León, Soraya (BioMed Central, 2014)
BACKGROUND: The OHIP-49 is widely used to assess oral health-related quality of life, but its length makes it time-consuming and difficult to use. An abbreviated version of the OHIP-49 with fourteen items has been validated for older adults, but not in Chile. The aim was to develop and validate the Spanish version of the OHIP-14 in an elderly Chilean population. METHODS: Two studies were conducted; a cross sectional to develop and a retrospective study to validate the OHIP-14Sp. The OHIP-49Sp was applied to 490 older adults and the fourteen questions with the higher impact on oral health-related quality of life were selected through linear regression. These items were applied on a retrospective dataset of 85 older adults to test internal consistency (Cronbach’s alpha). A discriminative validity analysis was performed along with the assessment of sociodemographic (age and gender, educational level) and clinical variables (number of teeth, caries lesions, CPITN, prosthetic needs and prosthetic functionality). Data were analyzed using Mann–Whitney U, Student’s t and one-way ANOVA tests with a 95% confidence level and finally were analyzed by a Multivariate Logistic Regression Model. RESULTS: High internal consistency values were obtained for the OHIP-14Sp instrument (0.91). There was an association between the OHIP-14Sp scores and the presence of caries (p = 0.003), need for complex periodontal treatment (p = 0.002), prosthetic needs (p < 0.0001) and age younger than 70 years-old (p < 0.0001). Subjects with periodontal treatment need were more likely to report reduced oral health-related quality of life (PR = 2.10). CONCLUSIONS: The OHIP-14Sp proved to be a consistent and valid tool to assess oral health-related quality of life when tested in Chilean older adults.